2021
DOI: 10.1155/2021/9613102
|View full text |Cite
|
Sign up to set email alerts
|

Urban Landscape Information Atlas and Model System Based on Remote Sensing Images

Abstract: City landscape is an element of city image, and city landscape logo should also belong to the entire system of the city image logo. Since the reform and opening up, China’s economic construction industry has attracted worldwide attention, and the improvement of people’s living standards has led to the continuous development of urban construction. The original urban style is gradually replaced by high-rise buildings, the differences between cities are getting smaller and smaller, and the people living in them h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Shan et al found that the definition of the so-called enterprise information management is to adopt digital processing for all steps in the operation of the enterprise and use the current computer information technology for integrated processing, which is conducive to improving the work efficiency of the enterprise, the development of the global economy, and the core competitiveness of the enterprise [5]. Hu and Gong found that since the twenty-first century, most of the European and American countries led by the United States and Britain have realized enterprise information management, which can increase the competitive strength of enterprises [6]. Deng et al believe that China has experienced more than 30 years of reform, opening up and modernization, and has made great progress in information management [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shan et al found that the definition of the so-called enterprise information management is to adopt digital processing for all steps in the operation of the enterprise and use the current computer information technology for integrated processing, which is conducive to improving the work efficiency of the enterprise, the development of the global economy, and the core competitiveness of the enterprise [5]. Hu and Gong found that since the twenty-first century, most of the European and American countries led by the United States and Britain have realized enterprise information management, which can increase the competitive strength of enterprises [6]. Deng et al believe that China has experienced more than 30 years of reform, opening up and modernization, and has made great progress in information management [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the virtual reality technology provides an environment enabling agricultural students to enhance their talents [58]. Another key technology is remote sensing used to study urban landscape-based systems in the process of urban development [59]. Similarly, fuzzy logic has also been applied to build a system for the management of environmental damage [60] as well as conservation of parrot species using transfer learning [61].…”
Section: Prior Artmentioning
confidence: 99%
“…(2) Extraction of spatial structure features from the village genetic data Similar to a geographic information graph, the characteristic village genetic data graph is established upon a GIS database and is categorized based on the predominant functions of each village. It involves the extraction of an array of combinations comprising graphics, textual data, numerical information, and models [40]. This paper draws upon methodologies used in creating geographical information graphs, traditional village landscape genetic data graphs, and regional cultural heritage landscape gene graphs.…”
Section: Research Methods and Construction Framework Of The Spatial S...mentioning
confidence: 99%